Construction of a porous-ionic-polymer encapsulated Rh-TPPTS catalyst for regioselective hydroformylation - Sen Feng; Cunyao Li; Guifa Long; Guangjun Ji; Xiaofeng Ma; Benhan Fan; Hong Wei; Xinyuan Liu; Yang Zhao; Miao Jiang; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2026)

Structure-process-performance: A systematic framework for deconstructing constructed wetland models - Hai Long Kang; Yin Yang; Sen Yang; Xin Yao; Hui Jiang; Wen-Bo Nie (Water Research, 2026)

Study on defluorination performance and mechanism of Fe-Al modified oyster shell substrate coupled with microbially induced calcium precipitation for enhanced ecological floating beds - Sen Wang; Xueqi Wang; Yile Dai; Long Yang; Jingxin Song; Junqi Sun; Chunyan Zhai; Fanlong Kong; Shuo Li; Jiaxin Shi (Journal of Hazardous Materials, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Atmospheric mechanisms and kinetics of hydroperoxymethyl formate reactions with OH and Criegee intermediates - Sen Yang; Bo Long (Atmospheric Environment, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Effect of pile foundation on seismic response of adjacent subway station buried in sand site by centrifuge shaking table tests - Long-Ji Zhang; Zhen-Dong Cui; Meng-Hui Huang; Jia-Sen Yan; Su-Yang Wang (Engineering Structures, 2026)

Static and dynamic responses of a novel UEST column under axial compression and wave force - Yun-Long Chen; Jing-Zhong Tong; Li-Sen Zheng; Chao-Qun Yu (Ocean Engineering, 2026)

Functional traits are plastic in response to intercropping, improving the stability of yield through temporal asynchrony - Hao Yang; Wei-Ping Zhang; Surigaoge Surigaoge; Hua-Sen Xu; Ye Su; Ragan M. Callaway; Long Li (Field Crops Research, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

First report of Thraustochytrium caudivorum isolated from the undulated surf clam (Paratapes undulatus): Morphological, molecular, and ecological insights under climate change - Yu Chen; Seung-Hyeon Kim; Jinxia Long; S.D.N.K. Bathige; Hyoun Joong Kim; Sen-Lin Tang; Kyung-Il Park (Protist, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Synergistic pollution and carbon emission reductions via constructed wetland coupled microbial fuel cell: A critical review - Huazhen Wu; Hong Yang; Guoxian Yang; Long Yang; Xin Chen; Xiaohan Ma; Chenguang Wang; Chunyan Zhai; Xiaotong Wang; Fanlong Kong; Sen Wang (Journal of Water Process Engineering, 2025)

Removal of emerging organic contaminants in a subsurface wastewater infiltration system: A preliminary study of microbial mechanism - Feng-Jiao Peng; Xing-Jun Feng; Sen Li; Xiao-Long Yu; Jun Chen; Shuang-Shuang Liu; Guang-Guo Ying; You-Sheng Liu (Water Research, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Lanthanum supplementation at the heading stage efficiently reduces cadmium content in rice by regulating key genes involved in cadmium uptake, translocation, and redistribution pathways - Hua Yang; Jie Li; Caixia Xiao; Jian Long; Sen Li; Shuai Zhang; Zhiting Xiong (Environmental Pollution, 2025)

Mechanisms of chemical corrosion in alumina-chromite refractories during e-waste recovery via pyrometallurgy - Shiliang Chen; Jian Wu; Xin Wang; Youqi Fan; Yuntao Yan; Xiutao Guan; Zhipeng Guo; Sen Zhao; Wenlong Tan; Chao Ding; Hongming Long (Journal of Environmental Chemical Engineering, 2025)

Methane hydrate formation kinetics and structure information in the presence of cyclopentane under different reaction evolution - Wen-Zhe Sun; Hai-Long Liu; Kai Zhang; Xu-Ke Ruan; Yi-Song Yu; Xiao-Sen Li (Chemical Engineering Journal, 2025)

Red princess of the Silk Road - the first-and-only known case of cinnabar-stained teeth in antiquity from the Iron Age Western Regions (202BCE − 8CE) - Sen You; Meng Ren; Li Sun; Anqi Wang; Long Wang; Quanchao Zhang; Qian Wang (Archaeological and Anthropological Sciences, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Unveiling Frequency-Specific Microstate Correlates of Anxiety and Depression Symptoms - Siyang Xue; Xinke Shen; Dan Zhang; Zhenhua Sang; Qiting Long; Sen Song; Jian Wu (Brain Topography, 2025)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Exploring the biphasic dose-response effects of photobiomodulation on the viability, migration, and extracellular vesicle secretion of human adipose mesenchymal stem cells - Che-Yi Chang; Ana Elena Aviña; Cheng-Jen Chang; Long-Sheng Lu; Yi-Yong Chong; Tzu Ying Ho; Tzu-Sen Yang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Simultaneous characterization and quantification of 25 flavonoid compounds in Actinidia arguta Miq. leaves by HPLC-DAD and screening for their inhibitory activity on α‑glucosidase - Yu-Fei Hou; Lu Bai; Shao-Jing Liu; Sen Guo; Ya-Long Wang; Chi-Tang Ho; Nai-Sheng Bai (Phytochemistry Letters, 2024)

Single-Cell Sequencing Technology and Its Application in the Study of Central Nervous System Diseases - Yang Ding; Yu-Yuan Peng; Sen Li; Can Tang; Jie Gao; Hai-Yan Wang; Zai-Yun Long; Xiu-Min Lu; Yong-Tang Wang (Cell Biochemistry and Biophysics, 2024)

Tetrabromobisphenol A and hexabromocyclododecane in sediments from the Zhujiang (Pearl) River Estuary and South China Sea - Chuyue Long; Weiyan Yang; Jiaxun Lu; Yuanyue Cheng; Ning Qiu; Sen Du; Li Zhang; Shejun Chen; Yuxin Sun (Acta Oceanologica Sinica, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

Synergistic cytotoxicity of decitabine and YM155 in leukemia cells through upregulation of SLC35F2 and suppression of MCL1 and survivin expression - Jing-Ting Chiou; Long-Sen Chang (Apoptosis, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Thermal Contact Resistance of Granite Joints Under Normal Stress - Zheng-Wei Li; Meng-Cheng Long; Peng Xu; Chuan-Yuan Huang; Yun-Sen Wang (Rock Mechanics and Rock Engineering, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Amsacrine downregulates BCL2L1 expression and triggers apoptosis in human chronic myeloid leukemia cells through the SIDT2/NOX4/ERK/HuR pathway - Yuan-Chin Lee; Jing-Ting Chiou; Liang-Jun Wang; Ying-Jung Chen; Long-Sen Chang (Toxicology and Applied Pharmacology, 2023)

Inhibition of AT1R/IP3/IP3R-mediated Ca2+ release protects against calcium oxalate crystals-induced renal oxidative stress - Sen-Yuan Hong; Yuan-Yuan Yang; Shao-Gang Wang; Bao-Long Qin (Chemico-Biological Interactions, 2023)

miRNAs contributing to the repair of tendon injury - Kexin Lyu; Xinyue Liu; Tianzhu Liu; Jingwei Lu; Li Jiang; Yixuan Chen; Longhai Long; Xiaoqiang Wang; Houyin Shi; Fan Wang; Sen Li (Cell and Tissue Research, 2023)
Tendon injury is one of the most common disorders of the musculoskeletal system, with a higher likelihood of occurrence in elderly individuals and athletes. In posthealing tendons, two undesirable consequences, tissue fibrosis and a reduction in mechanical properties, usually occur, resulting in an increased probability of rerupture or reinjury; thus, it is necessary to propose an appropriate treatment. Currently, most methods do not sufficiently modulate the tendon healing process and restore the function and structure of the injured tendon to those of a normal tendon, since there is still inadequate information about the effects of multiple cellular and other relevant signaling pathways on tendon healing and how the expression of their components is regulated. microRNAs are vital targets for promoting tendon repair and can modulate the expression of biological components in signaling pathways involved in various physiological and pathological responses. miRNAs are a type of noncoding ribonucleic acid essential for regulating processes such as cell proliferation, differentiation, migration and apoptosis; inflammatory responses; vascularization; fibrosis; and tissue repair. This article focuses on the biogenesis response of miRNAs while presenting their mechanisms in tendon healing with perspectives and suggestions.

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Allergenicity of wheat protein in diet: Mechanisms, modifications and challenges - Ming Liu; Jihong Huang; Sen Ma; Guanghai Yu; Aimei Liao; Long Pan; Yinchen Hou (Food Research International, 2023)

Identification of genetic loci associated with five agronomic traits in alfalfa using multi-environment trials - Sen Lin; Cesar A. Medina; Guojie Wang; David Combs; Glenn Shewmaker; Steve Fransen; Don Llewellyn; Steven Norberg; Long-Xi Yu (Theoretical and Applied Genetics, 2023)

Osmoregulation, physiological metabolism, and oxidative stress responses to water salinity in adult males of Chinese mitten crabs (Eriocheir sinensis) - Xin Wang; Zhi-xin Guo; Xin-yu Lei; Sen Wang; Ji-wu Wan; Hong-jian Liu; Yu-ke Chen; Yun-long Zhao; Gui-qin Wang; Qiu-ju Wang; Dong-ming Zhang (Aquaculture International, 2023)

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Noninvasive oral cancer screening based on local residual adaptation network using optical coherence tomography - Wei Yuan; Long Cheng; Jinsuo Yang; Boya Yin; Xingyu Fan; Jing Yang; Sen Li; Jianjun Zhong; Xin Huang (Medical & Biological Engineering & Computing, 2022)

Effects of different stocking densities on the growth performance and antioxidant capacity of Chinese mitten crab (Eriocheir sinensis) in rice crab culture system - Xin Wang; Qi Yao; Xin-yu Lei; Dong-ming Zhang; Sen Wang; Ji-wu Wan; Hong-jian Liu; Yu-ke Chen; Yun-long Zhao; Gui-qin Wang; Qiu-ju Wang; Zhi-xin Guo (Aquaculture International, 2022)

First report of leaf spot on Prunus salicina caused by Alternaria alternata in China - Haijiang Long; Sen Yang; Xianhui Yin; Zhibo Zhao; Youhua Long; Juan Fan; Ran Shu; Guifei Gu (Journal of Plant Pathology, 2021)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Amsacrine-induced apoptosis of human leukemia U937 cells is mediated by the inhibition of AKT- and ERK-induced stabilization of MCL1 - Yuan-Chin Lee; Ying-Jung Chen; Chia-Hui Huang; Long-Sen Chang (Apoptosis, 2017)

Hydroquinone-induced FOXP3-ADAM17-Lyn-Akt-p21 signaling axis promotes malignant progression of human leukemia U937 cells - Ying-Jung Chen; Wen-Hsin Liu; Long-Sen Chang (Archives of Toxicology, 2017)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Erythropoietin Attenuates the Apoptosis of Adult Neurons After Brachial Plexus Root Avulsion by Downregulating JNK Phosphorylation and c-Jun Expression and Inhibiting c-PARP Cleavage - Kai Li; Rang-Juan Cao; Xiao-Juan Zhu; Xing-Yu Liu; Long-Yun Li; Shu-Sen Cui (Journal of Molecular Neuroscience, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Naphtho[1,2-b]furan-4,5-dione inhibits MDA-MB-231 cell migration and invasion by suppressing Src-mediated signaling pathways - Pei-Chien Tsai; Chiao-Lun Chu; Yaw-Syan Fu; Chih-Hua Tseng; Yeh-long Chen; Long-Sen Chang; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2014)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Quercetin modulates activities of Taiwan cobra phospholipase A2 via its effects on membrane structure and membrane-bound mode of phospholipase A2 - Yi-Ling Chiou; Shinne-Ren Lin; Wan-Ping Hu; Long-Sen Chang (Journal of Biosciences, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Guanidination of notexin alters its membrane-damaging activity in response to sphingomyelin and cholesterol - Pei-Hsiu Kao; Yi-Ling Chiou; Shinne-Ren Lin; Long-Sen Chang (Journal of Biosciences, 2010)

Trichosanthin inhibits integration of human immunodeficiency virus type 1 through depurinating the long-terminal repeats - Wen-Long Zhao; Du Feng; Ju Wu; Sen-Fang Sui (Molecular Biology Reports, 2010)

Functional role of EF-hands 3 and 4 in membrane-binding of KChIP1 - Yan-Shun Liao; Ku-Chung Chen; Long-Sen Chang (Journal of Biosciences, 2009)

Molecular Cloning and Evolution of the Genes Encoding the Precursors of Taiwan Cobra Cardiotoxin and Cardiotoxin-Like Basic Protein - Long-Sen Chang; Shu-Kai Lin; Charling Chung (Biochemical Genetics, 2004)

Organization and Phylogenetic Analysis of κ-Bungarotoxin Genes from Bungarus Multicinctus (Taiwan Banded Krait) - Long-sen Chang; Charling Chung; Jordge Lin; Enjong Hong (Genetica, 2002)

Kinetic Measurements of Cell Surface E-Selectin/Carbohydrate Ligand Interactions - Mian Long; Hong Zhao; Kuo-Sen Huang; Cheng Zhu (Annals of Biomedical Engineering, 2001)